2016
DOI: 10.21511/ppm.14(3-1).2016.05
|View full text |Cite
|
Sign up to set email alerts
|

Social values as determinants of entrepreneurial intentions among university students in Cape Town – South Africa

Abstract: An empirical study was conducted in Cape Town -South Africa -to determine whether social values (family, parents' work and education) have an impact on entrepreneurship students in the universities of Cape Town, University of Stellenbosch, and University of the Western Cape, as well as Cape Peninsula University of Technology. The paper reviewed the literature about the role social values plays in the people's lives. Respondents were the entrepreneurship university students. Data were collected in classrooms, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The results found that there is a significant correlation between the 2 variables. The findings confirmed the existing research which inferred that social valuation like family support and peer support induce entrepreneurial intention (Sanditov & Verspagen, 2011;Fatoki, 2010;Kalitanyi et al, 2016;Bagus et al, 2021;Sahban et al, 2016;Suharti & Sirine, 2021;Zafar et al, 2012). The support, guidance, and assistance provided by family members, friends, peers, and affiliates influence one's decision to venture into entrepreneurship.…”
Section: Analysis and Findingssupporting
confidence: 89%
“…The results found that there is a significant correlation between the 2 variables. The findings confirmed the existing research which inferred that social valuation like family support and peer support induce entrepreneurial intention (Sanditov & Verspagen, 2011;Fatoki, 2010;Kalitanyi et al, 2016;Bagus et al, 2021;Sahban et al, 2016;Suharti & Sirine, 2021;Zafar et al, 2012). The support, guidance, and assistance provided by family members, friends, peers, and affiliates influence one's decision to venture into entrepreneurship.…”
Section: Analysis and Findingssupporting
confidence: 89%
“…The entrepreneurship intentions of students are influenced by demographic factors (Father's occupation, Gender, Experience and Level of education) (Mohammad Ahmar Uddin, Shariq Mohammad, & Samir Hammami, 2016). Social values also have an impact on the entrepreneurship intentions (Kalitanyi & Visser, 2016). Harris and Gibson (2008) report that the role of the university is important for fostering students start-up activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extending the intention argument of several researchers, such as [5,73,74], is the link to social values [75]. [75] characterise social value in this regard to suggest the exposure a student gets when exposed to an entrepreneurial family.…”
Section: Social Valuesmentioning
confidence: 99%